1989
DOI: 10.1093/schbul/15.3.441
|View full text |Cite
|
Sign up to set email alerts
|

Physical Mapping, Linkage Analysis of a Putative Schizophrenia Locus on Chromosome 5q

Abstract: Two recent studies have suggested that a schizophrenia susceptibility locus may lie on the proximal long arm of chromosome 5. Partial trisomy of a 20-30 centimorgan region of chromosome 5 (5q11.2-13.3) was found to cosegregate with schizophrenia in a Canadian family of Chinese descent. Moreover, DNA markers from proximal 5q (D5S39, D5S76) were found to be linked to schizophrenia and related disorders in seven British and Icelandic families. We now report an initial physical map of DNA markers relative to the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

1990
1990
1996
1996

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(10 citation statements)
references
References 41 publications
0
10
0
Order By: Relevance
“…Early reports from Bassatt et al [1988] and Sherrington et al [1988] suggested that loci on the long arm of chromosome 5 might be related to the expression of schizophrenia [Bassatt et al, 1988;Sherrington et al, 19881, although subsequent studies, including one from Sherrington et al [1988] could not confirm this [Kennedy et al, 1988;St. Clair et al, 1989;Hallmayer et al, 1992;Macciardi et al, 1992;Detera-Wadleigh et al, 1989;Aschauer et a]., 1990;McGuffin et al, 1990;Kaufman et al, 1989;Gurling, 19941. Overall, less attention has been focused on the short arm of chromosome 5, but while some studies have rejected linkage to various loci there [Kennedy et al, 1989;Coon et al, 19941, a carrier of a normal balanced chromosome 5 translocation (5: 141, including sections from both arms around the centromere (p14.1:q32.3), produced 5 offspring, 2 of whom had a partial 5p trisomy, one with schizophrenia the other with refractory epilepsy [Malaspina et al, 19921. We report evidence for linkage to the D 5 S l l l locus (5~14.1-p13.1) and other markers on the short arm of chromosome 5 in one large kindred, whose members were diagnosed using strictly defined predetermined criteria for the schizophrenia-related phenotype.…”
Section: Introductionmentioning
confidence: 99%
“…Early reports from Bassatt et al [1988] and Sherrington et al [1988] suggested that loci on the long arm of chromosome 5 might be related to the expression of schizophrenia [Bassatt et al, 1988;Sherrington et al, 19881, although subsequent studies, including one from Sherrington et al [1988] could not confirm this [Kennedy et al, 1988;St. Clair et al, 1989;Hallmayer et al, 1992;Macciardi et al, 1992;Detera-Wadleigh et al, 1989;Aschauer et a]., 1990;McGuffin et al, 1990;Kaufman et al, 1989;Gurling, 19941. Overall, less attention has been focused on the short arm of chromosome 5, but while some studies have rejected linkage to various loci there [Kennedy et al, 1989;Coon et al, 19941, a carrier of a normal balanced chromosome 5 translocation (5: 141, including sections from both arms around the centromere (p14.1:q32.3), produced 5 offspring, 2 of whom had a partial 5p trisomy, one with schizophrenia the other with refractory epilepsy [Malaspina et al, 19921. We report evidence for linkage to the D 5 S l l l locus (5~14.1-p13.1) and other markers on the short arm of chromosome 5 in one large kindred, whose members were diagnosed using strictly defined predetermined criteria for the schizophrenia-related phenotype.…”
Section: Introductionmentioning
confidence: 99%
“…Shemngton et al [1988], 15 from St. Claire et al[1989], 5 from Detera-Wadleigh et al[1989], 4 fromKaufmann et al [1989], 6 fromMcGuffin et al [1990], 7 fromAschauer et al [1990], and6 fromCroweeta1. [1991].…”
mentioning
confidence: 99%
“…Subsequent studies (Kennedy et al, 1988;St. Clair et al, 1989;Detera-Wadleigh et al, 1989;Kaufman et aL, 1989;Aschauer et al, 1990;Crowe et al, 1990;McGuffin et al, 1990;Blackwood et aL, 1991a;Hallmayer et aL, 1992) in other families, however, have found no evidence for linkage of schizophrenia to the 5ql 1.2-q13.3 location.…”
Section: Israeli Family Studiesmentioning
confidence: 99%
“…For example, initial findings of linkage in studies of schizophrenia (Sherrington et al, 1988) and bipolar disorder (Egeland et al, 1987) have not been replicated in subsequent studies (Kennedy et al, 1988;St. Clair et al, 1989;Detera-Wadleigh et al, 1989;Kaufman et aL, 1989;Aschauer et al, 1990;Crowe et al, 1990;McGuffin et al, 1990;Blackwood et al, 1991a;Hallmayer et al, 1992).…”
Section: From Nosology To Phenotypementioning
confidence: 99%